Visceral pain and visceral hypersensitivity - Gebhart, Gerald (Henry Stewart Talks, 2009)
Visceral Pain, Diffuse, referred and typically difficult to manage, Visceral Hypersensitivity, Defining characteristic of functional gastrointestinal disorders, Contributed to by both peripheral and central mechanisms